Fc-Independent Phagocytosis: Implications for Intravenous IgG Therapy in Immune Thrombocytopenia - Webster, Michelle L.; Zhu, Guangheng; Li, Yan; Ni, Heyu (Cardiovascular & Haematological Disorders - Drug Targets, 2008)
Phagocytes were first described 120 years ago. Although the molecular mechanisms involved in initiating phagocytosis (through Fc or other receptors) are still not fully understood, the roles of phagocytes in innate and adaptive immunity have been well studied. Phagocytes in the reticuloendothelial system, particularly macrophages, have been implicated in the clearance of senescent blood cells. The destruction of these cells may be primarily mediated through an Fcindependent pathway. Fc-independent phagocytosis may also play an important role in platelet clearance, including immune thrombocytopenia (ITP). The two major platelet antigens targeted in ITP are GPIIbIIIa and the GPIb complex. It has been demonstrated that anti-GPIbα antibodies, in contrast to anti-GPIIbIIIa, can induce thrombocytopenia in an Fcindependent manner. We further demonstrated in an animal model that intravenous IgG is not able to ameliorate thrombocytopenia caused by most anti-GPIbα antibodies, though it is effective in anti-GPIIbIIIa mediated thrombocytopenia. Our data was supported by a recent retrospective study of ITP patients. Therefore, identification of antibody specificity (e.g. anti-GPIIbIIIa (Fc-dependent) versus anti-GPIbα (Fc-independent)) in patients may be important for ITP therapy.
Keywords: intravenous IgG